DAMPAK PENGGUNAAN GADGET TERHADAP PERKEMBANGAN BAHASA ANAK USIA DINI - Basrah, Basrah; Rusmayadi, Rusmayadi; Musi, Muhammad Akil; Halik, Abd (MAJU : Indonesian Journal of Community Empowerment, 2025)
This research wants to find out about the impact of gadget use on early childhood development at an early age. The purpose of this research is to describe early childhood language skills at the age of speaking and listening/listening. This research is a qualitative research using a descriptive method. The subject of this study is early childhood at the age of 4-5 years The results of this study show that there are some children who have not been able to express language well so that in the category they have not developed, this can be seen from children who have not been able to answer questions according to the questions, have not even been able to express their feelings with adjectives and have not been able to express their opinions to others. Meanwhile, some other children have begun to be able to express language well enough so that they are categorized as beginning to develop. The obstacles faced so that the development of early childhood language is hampered obtained from the results of parent interviews, namely due to the lack of firmness and supervision of the use of children's gadgets from parents.